Numerical techniques for proton magnetometers - Patil, A.; Rajaram, R. (My University, 2002)
The problem of estimation of the precession frequency of the proton magnetometer has been addressed here. The precession frequency has to be determined from the successive zero crossings of the sinusoidal output signal induced in the coil by the proton rich fluid immersed in the earth's magnetic field. The dependence of the accuracy of the signal to noise ratio and decay of the signal is discussed. Least square methods and the robust median fit methods are used to estimate the signal period. It is found that the signal processing method using a robust technique gives superior performance when higher sampling is needed or the environmental conditions degrade the available signal to noise ration. For a five second sampling under ideal observatory conditions, even the least square technique provides a 0.1 nT accuracy.
Keywords: Geomagnetic instruments; Proton magnetometers; IAGA workshop; Data acquisition